2020
DOI: 10.3390/nu12082316
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence on the Efficacy of Gluten-Free Diets in Multiple Sclerosis, Psoriasis, Type 1 Diabetes and Autoimmune Thyroid Diseases

Abstract: In this review, we summarize the clinical data addressing a potential role for gluten in multiple sclerosis (MS), psoriasis, type 1 diabetes (T1D) and autoimmune thyroid diseases (ATDs). Furthermore, data on the prevalence of celiac disease (CD) and gluten-related antibodies in the above patient groups are presented. Adequately powered and properly controlled intervention trials investigating the effects of a gluten-free diet (GFD) in non-celiac patients with MS, psoriasis, T1D or ATDs are lacking. Only one cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 186 publications
(239 reference statements)
0
39
0
3
Order By: Relevance
“…However, some authors reported a higher prevalence of anti-gliadin immunoglobulins (AGA) or immunoglobulin against tissue transglutaminase (IgA-tTG, IgG-tTG) in pwMS, whereas similar antibody levels between pwMS and healthy controls were revealed by others [90]. Furthermore, several studies investigated the prevalence and the risk to develop MS in patients with CD failing to show a significant association [91]. The benefit of GFD with respect to a free diet among pwMS has been investigated only by a single, non-randomized trial, suggesting a significant lower activity on magnetic resonance imaging (MRI) and lower EDSS scores [92].…”
Section: Gluten-free Diet (Gfd)mentioning
confidence: 98%
“…However, some authors reported a higher prevalence of anti-gliadin immunoglobulins (AGA) or immunoglobulin against tissue transglutaminase (IgA-tTG, IgG-tTG) in pwMS, whereas similar antibody levels between pwMS and healthy controls were revealed by others [90]. Furthermore, several studies investigated the prevalence and the risk to develop MS in patients with CD failing to show a significant association [91]. The benefit of GFD with respect to a free diet among pwMS has been investigated only by a single, non-randomized trial, suggesting a significant lower activity on magnetic resonance imaging (MRI) and lower EDSS scores [92].…”
Section: Gluten-free Diet (Gfd)mentioning
confidence: 98%
“…Indeed, gliadin may induce immune responses, which are related to autoimmunity. 9,38,39 Our results showed the elevated levels of IFN-γ and IL-17 and upregulation of inflammatory chemokines CXCL-2, CCL-2, and CXCL-10 in further analysis for evaluating the possible mechanism of neurological complications after gliadin immunization, which played essential roles in leukocyte trafficking. These data could be considered as possible immune-mediated responses against gliadin.…”
Section: Discussionmentioning
confidence: 63%
“…Large population studies on patients with CD do not confirm the beneficial effect of GFDs on the autoimmune process in HT, and so caution is advised when prescribing a GFD to patients with cAITD [ 37 ]. It seems that it is not so much the GFD itself as general diet modification (including nutrition education and healthy dietary habits promotion, such as increased fiber consumption) that may play an important role in the GFDG, especially in terms of improving the absorption of levothyroxine from the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%